Políticas sociais: o processo de organização dos catadores de materiais recicláveis - Barreto, Jonatas dos Santos (2017)
The present study aims to analyze the work process and organization of recyclable waste pickers, as well as the articulation of Public Policies, specifically the Social Assistance and Environment Policy. In this context we will analyze the evolution of the National Collectors Movement, the struggle for the guarantee of social rights and the recognition of the professional category. The Solidarity Economy Movement presents itself from the perspective of grassroots formations through Solidary Popular Education, playing an important role in the process of organizing the collectors. In order to reach the objectives, the research was divided in two stages, the first one: Empirical Observation, Documentary and Bibliographic Research, the second stage in Exploratory Research through the application of data collection instruments, questionnaire and interviews, together with Cooperative Collectors of Recyclable Materials (COOTACAR). Analyzing the specific objectives, we identified the main problems faced by the collectors in the daily life of their work, we know the life history of the collectors and their difficulties, the conjuncture of the Municipal Program of Selective Collection of Cascavel / PR, we evaluate the limits and possibilities of the cooperative ; Demonstrating the advance and retreat in front of the organizational process.